Efektivitas Program Inkubasi Terhadap Perkembangan Wirausaha - Puteri Amalia; Risnawati Risnawati; Harnida Wahyuni Adda; Fera Fera (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Economic growth programs are a series of policies, strategies, and initiatives designed by the government to stimulate, improve, and accelerate economic growth. The Incubation Program is one of the government programs and related institutions that can support and increase the number and quality of entrepreneurs in various sectors through coaching, mentoring and development. The Incubation Program Effectiveness research aims to determine the effectiveness of the Incubation Program implementation on the development of entrepreneurs assisted by IBTI Maleo Techno Center. The location of this research is IBTI Maleo Techno Center. This research discusses the indicators that influence the effectiveness of the Incubation Program on the development of IBTI Maleo Techno Center's fostered entrepreneurs. In this research, the author uses qualitative research methods through primary and secondary data collection obtained through literature study and interviews. After the data is collected, it is then analyzed and conclusions are drawn using the method of Miles and Hubberman. The results showed that the effectiveness of the Incubation Program on the development of IBTI Maleo Techno Center's fostered entrepreneurs was considered effective in accordance with Sutrisno's effectiveness measurement.